Is there an association between anxiety/depression and temporomandibular disorders in college students? - Leticia Bojikian CALIXTRE; Bruno Leonardo da Silva GRUNINGER; Thais Cristina CHAVES; Ana Beatriz de OLIVEIRA (University of São Paulo, 2014)
Objective: Considering the high incidence of Temporomandibular Disorders (TMD) in the population aged 15-30 years and the fact that students are exposed to stressful psychosocial factors, the purposes of this study were: to verify clinical symptoms and jaw functionality in college students with TMD according to the anxiety/depression (A/D) level and to evaluate the correlation between A/D and functionality, maximum mouth opening (MMO) and pain and muscle activity. Material and Methods: Nineteen students with TMD diagnosed according to the Research Diagnostic Criteria for Temporomandibular Disorders underwent two assessments during an academic semester. The evaluations were based on questionnaires (MFIQ - Mandibular Function Impairment Questionnaire; HADS - Hospital Anxiety and Depression Scale), clinical measurements (MMO without pain, MMO and assisted MMO; palpation of joint and masticatory muscles), and electromyography. The HADS scores obtained in the two assessments were used to classify all data as either "high" or "low" A/D. Data normality, differences and correlations were tested with the Shapiro-Wilk test, Student's t-test (or the Wilcoxon test), and Spearman test, respectively. The alpha level was set at 0.05. Results: None of the clinical variables were significantly different when comparing low and high A/D data. In low A/D there was a significant correlation between HADS score and: MFIQ (P=0.005, r=0.61), and MMO without pain (P=0.01, r=-0.55). Conclusions: Variation in A/D level did not change clinical symptoms or jaw functionality in college students with TMD. Apparently, there is a correlation between TMJ functionality and A/D level, which should be further investigated, taking into account the source of the TMD and including subjects with greater functional limitation.